Dampak PSAK 71, 72, 73 di Perusahaan Multinasional - Kristin, Dewi; Kurnia, Deswita Mila; Yandari, Aprilya Dwi (Unversitas Islam Madura, 2024)
This research analyzes the impact. of implementing. PSAK 71, 72, and 73 on multinational companies. The background phenomenon is the harmonization of Indonesian accounting standards with IFRS, which affects the financial reporting of multinational companies. Thel aim lof thisl research isl to levaluate significant changesl lin financial reporting and company performance due to the implementation of these standards. Thel method lused is la qualitativel approach basedl onl literature studies of 30 related journals. The research results show that PSAK 71 increases the allowance for impairment losses by up to 50% and changes the capital adequacy ratio (CAR) and profitability (ROA). PSAK 72 refines revenue recognition through a five-step model, increasing the transparency of financial statements. PSAK 73 requires capitalization of leased assets, which impacts capital structure and financial ratios. The main conclusion is that these standards increase the transparency, relevance and comparability of financial reports, but require significant adaptations in technology and corporate resources.